Spatial distribution of heavy metals in the Ga- Selati River of the Olifants River System, South Africa - Addo-Bediako, Abraham; Rasifudi, Lwendo (Informa UK Limited, trading as Taylor & Francis Group, 2021)
The Ga-Selati River is subjected to different forms of pollution from mining, industrial and agricultural activities, and human settlements. The objectives of the study were to assess heavy metal pollution and to determine possible sources of pollutants in the river. Water and sediment samples were collected and analysed for the following selected metals: arsenic (As), chromium (Cr), iron (Fe), manganese (Mn), nickel (Ni) and zinc (Zn) using sequential Inductively Coupled Plasma-optical emission spectrometry (ICP-OES). The enrichment factor (EF) and geoaccumulation index (Igeo) were used to determine the level of metal pollution in the sediment. The results indicated that Cr and Ni were the most accumulated elements in the sediments, and the midstream sites (S4 and S5) showed a much higher pollution level than the upstream and downstream sites. The main sources of pollutants were mining, wastewater/sewage and agricultural discharges. This may pose a serious threat to the river and health risk to the nearby rural communities, which rely on the river, especially for drinking water. Proper management strategies to reduce pollution is therefore necessary.
Journal article published in the Journal of Chemistry and Ecology 2021, VOL. 37, NO. 5, 450–463
Keywords: Heavy metals; Pollution; Nutrients; Geo-accumulation; Sediment; Water quality; Heavy metals; Waste disposal in rivers, lakes, etc.; Water -- Pollution; Water quality -- South Africa -- Limpopo